(untitled) (International Journal of Engineering and Computer Science, 2014)
Delay Tolerant Networks are the network where the continuous network connectivity is lacking. R-CAR algorithm[2] addresses the issue of routing in such networks. But the paper fails to address issues regarding newly arrived node in a network, prioritization of low hop count carrier node and sharing and dynamic updation of local reputation tables. This paper gives an Improved version (IRCAR) that efficiently solves these issues.